OPTIMALISASI PEMANTAUAN PERTUMBUHAN ANAK DI POSYANDU UMBULHARJO MELALUI PENGGUNAAN PERANGKAT ANTROPOMETRI IoT - Wahyu Sugianto; Herenda Sela Wismaya; Brevi Istu Pambudi (Universitas Mataram, 2026)
Stunting and underweight among children under five remain significant nutritional challenges in Indonesia, including in Sleman. These conditions are influenced by inadequate dietary intake, limited access to health services, and socioeconomic factors. Their long-term impact may hinder children's physical growth and cognitive development. Accurate growth monitoring is essential for early prevention of nutritional problems. This program aims to enhance community knowledge and skills in early detection of nutritional risks through the use of IoT-based anthropometric devices. The program involved problem identification, development of IoT anthropometric equipment, and training on device use for cadres and parents. Knowledge improvement was evaluated using Pre-Test and Post-Test scores analyzed with a paired t-test. Participants' knowledge increased by 12.3% based on the Pre-Test and Post-Test comparison. Cadres were able to operate the IoT anthropometric device independently and demonstrated good understanding during practice sessions. Participants showed high engagement, including four questions raised during discussions. The device provided real-time data and supported easier recording of child growth. Its implementation improved the accuracy of early detection of nutritional risks. The adoption of IoT-based anthropometric devices enhances early detection of nutritional problems and strengthens child growth monitoring at the Posyandu.